Coverage of national-ethnic conflicts in the information space of Kazakhstan - Kastay, Дастан; Bashanova, Құралай (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The main task of today's day is the optimal decision of the ethical and psychological problem, which is based on the main dogmas and historical policies in the public, from the anti-religious policies to the use of the functions of the mass media for the formation of a unique community, and the transition from intending to create a public setting for a unique national setting to transforming a public setting with the support of life and their people for the first stage of the story of the day. The research article identifies the impact of domestic media on maintaining social stability and enhancing citizens' legal literacy. Within the journalism field, there has been a notable surge in technical pragmatism, a substantial influx of researchers, and the emergence of new media. Key moments are the concretization of the indicators of modernization of national formation, the current position of the institutions of management of Kazakhstan's socialism, and the orientation of society on the principles of democracy. Scientific output Research: an assessment of the activities of mass communications in Kazakhstan during the formation process, the development or outpouring of national policies, and real public relations after the introduction of non-compliance; an assessment of important directions for domestic investments. The Kazakh people and other diasporas are consolidating mass information, drawing on the scientific and theoretical expertise of traditional and citizen journalism to explore ethnic conflicts. In addition, the scientific framework incorporates symbols of “elements of discrimination,” “ethnic egoism,” and “social conflict” found in radio, television, newspapers, magazines, and other new sources of mass information.